Idempotent elements of the semigroup B_X (D) defined by semilattice of the class ∑_2(X,5) (Моделювання, керування та інформаційні технології, 2025)
The article discusses complete semigroups of binary relations defined by semilattices of the class . It is described idempotent elements of complete semigroups of binary relations defined by semilattices of the class . In the case of finite semigroups, the formula for calculating idempotent elements is obtained. It is shown that the order of any subgroup  of a semigroup  does not exceed 2